Autonomy and armed separatism in South and Southeast Asia - Miller, Michelle Ann (Institute of Southeast Asian Studies, 2012)
Armed separatis insurgencies have created a real dilemma for many national governments of how much freedom to grant aggrieved minorities without releasing territorial sovereignty over the nationstate. This book examines different approaches that have been taken by seven states in South and Southeast Asia to try and resolve this dilemma through various offers of autonomy. Providing new insights into the condition under which autonomy arrangements exacerbate or alleviate the problem of armed separatism, this comprehensive book includes in-depth analysis of the circumstances that lead men and women to take up arms in an effort to remove themselves from the state's borders by creating their own independent polity.